Trend of Patients Attended at Emergency Department of Referral Neurosciences Hospital in Bangladesh (Journal of National Institute of Neurosciences Bangladesh, 2024)
Background: Emergency Department is very important place for the patient. Objective: The purpose of the present study was to assess the trend of patients attended at emergency department of referral neurosciences hospital in Bangladesh.Methodology: This was a retrospective study carried out from January 2018 to 2021. This study was carried out in the Department of Microbiology at National Institute of Neurosciences & Hospital, Dhaka, Bangladesh. National Institute of Neurosciences & Hospital, Dhaka has been started its journey from September, 2012. It is situated in the health hub of Sher-E-Bangla Nagar, Dhaka, Bangladesh. This is the only Govt. run tertiary care neuroscience center in Bangladesh. We are having specialized out patient service and 24×7 emergency service. Our 100 bedded comprehensive stroke unit is running. Detailed medical record for each of the study sample was obtained from the record office.Results: A total number of 180145 cases were found with the duration of three years. This data showed that the number of neurology patients were attended at emergency department of Neurology at National Institute of Neurosciences and Hospital. The trend of patients who were attended at emergency department was stedily increase from January to December of 2020. It was found that a total number of 4786 cases were attended at emergency Department of study place. Later, this trend was increased.Conclusion: In conclusion the trend is increase from 2019 to 2021.Journal of National Institute of Neurosciences Bangladesh, July 2023;9(2):122-126